Trends of Forming the Accounting and Analytical Management System in the Digital Economy - Hushko, Serhii; Kulishov, Volodymyr; Izmaylov, Yaroslav; Subačienė, Rasa (Buhalterinės apskaitos teorija ir praktika, 2019)
Recent trends of overall digitalisation challenges to find new approaches and improvement of information formation systems in different spheres. The trends also make impact on the tendency to develop common stereotypes of methods, accounting procedures, reporting forms, etc. which may be called identification. The identification of accounting systems in its essence - is the solution to the problem of harmonization of accounting at the international level. However, it is impossible to achieve complete identification. Everything that is done in this direction at the national level by accounting systems (standardization of reporting, convergence of national rules with international ones, convergence of evaluation and control systems, etc.) indicates a progressive trend in the processes of identification and harmonization of accounting systems. The purpose of the research is to evaluate the trends of forming the accounting and analytical management system in the digital economy. The research methods are comparison, systematisation and summarisation of information. Thus the main components of the accounting organization have been defined, among them: the technique of organizing and conducting accounting; methodological support of accounting and internal control. There is a need for generalization of modern achievements for the construction of the AAMS, the development of the company's development strategy in the light of work peculiarities in the digital economy. Authors identified, that there is a modification of the existing and emergence of modern requirements and tasks for the organization of accounting due to a focus on new users, transformation of motives and requests of all interested in the accounting information participants of international economic relations. Moreover, further improvement of the AAMS organization will enable to increase efficiency and raise productivity of economic activity.JEL code: M40
Keywords: accounting; digitalization; globalization; information; accounting organization; system; management; analysis